Penyelesaian Perselisihan Tenaga Kerja Kasus Adam Air Melalui Mediasi Pada Tahap Perundingan Tripatrit Berdasarkan Undang-Undang No. 2 Tahun 2004 - Diana Putong (Industrial Engineering Study Program, Pattimura University, 2012)
In the world of work relations with the Workers Employers greatly affect the appearance or not the dispute in the industrial relations. A dispute within the industrial relations exists in every country in the world including Indonesia. Labor issues, including one of the major problems in all the developed and developing countries. To set up industrial dispute settlement then comes the various regulations relating to the rights and obligations of workers and employers. In Indonesia, regulations governing the rights and obligations of workers and employers, including dispute resolution procedures in industrial relations is through Act Number 13 of 2003 on Labor, and Law Number 2 of 2004 concerning Industrial Relations Disputes Settlement (PPHI).